Method on Inverted Equation Derivation for Steady-State Condition of Electrical Power System - N. P. Badalyan (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A new method on construction of a node resistance Z-matrix without direct inversion of nonsingular square Y-matrix of complex node resistance in electrical power system is proposed in the paper.